2018
DOI: 10.1002/gj.3172
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical characterization, petrogenesis, and emplacement tectonics of Paleoproterozoic high‐Ti and low‐Ti mafic intrusive rocks from the western Arunachal Himalaya, northeastern India and their possible relation to the ~1.9 Ga LIP event of the Indian shield

Abstract: Paleoproterozoic mafic intrusive rocks from the western Arunachal Himalaya have been studied for understanding their petrogenesis and tectonic environment, in which they were emplaced, with the help of their bulk-rock major, trace, and rare-earth elements (REE) compositions. These mafic intrusive rocks, mostly small bodies of dykes, sills, and lenses, are exposed in the Higher as well as the Lesser Himalaya sequences. Geochemically, 2 suites of rocks are identified and grouped into high-titanium and low-titani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 76 publications
(135 reference statements)
1
10
0
Order By: Relevance
“…It is suggested that these two distinct geochemical groups of the intrusive rocks were derived from discrete mantle melts; one group from 20-25% melting in the spinel stability field (thinner lithosphere), whereas the other group was derived from ~5-10% melting of a similar mantle source but in garnet stability field (thicker lithosphere). Rashid et al (2019) have also studied metabasic rocks from Lesser Himalayan sequence, western Arunachal Pradesh, for their geochemistry and presented almost similar results as observed by Srivastava and Samal (2019).…”
Section: Geochemistrysupporting
confidence: 57%
See 2 more Smart Citations
“…It is suggested that these two distinct geochemical groups of the intrusive rocks were derived from discrete mantle melts; one group from 20-25% melting in the spinel stability field (thinner lithosphere), whereas the other group was derived from ~5-10% melting of a similar mantle source but in garnet stability field (thicker lithosphere). Rashid et al (2019) have also studied metabasic rocks from Lesser Himalayan sequence, western Arunachal Pradesh, for their geochemistry and presented almost similar results as observed by Srivastava and Samal (2019).…”
Section: Geochemistrysupporting
confidence: 57%
“…1.80-1.90 Ga mafic intrusive rocks within the Himalayan Mountain Range are also thought to be part of the shared ca. 1.85-1.90 Ga LIP event (Srivastava and Samal, 2019;Samal et al, 2019a,b).…”
Section: Geochronologymentioning
confidence: 98%
See 1 more Smart Citation
“…A number of 1.88-1.89 Ga mafic/ultramafic sills are widely intruded and well-exposed in the lower startigraphic horizons of the Proterozoic Cuddapah intracratonic basin (Anand et al 2003;French et al 2008) (see figure 1). It is suggested that these mafic/ultramafic sills are integral part of a widespread *1.88-1.89 Ga Large Igneous Province (LIP) (Ernst and Srivastava 2008;French et al 2008;Belica et al 2014;Srivastava et al 2014a;Srivastava and Samal 2019), identified as a plume derived Hampi-Bastanar LIP (Samal et al 2019). However, Sheppard et al (2017) have provided a range of emplacement ages (1864AE13 and 1858AE16 Ma) for the felsic tuffs from the upper part of the Tadpatri Formation suggesting a series of magmatic events for *30 Ma and argued for a nonplume origin.…”
Section: Introductionmentioning
confidence: 99%
“…1300 Ma. Similarly, Srivastava and Samal (2019) analyzed mafic intrusive bodies from the Lesser and Higher Himalayas between Bomdila and Tawang in western Arunachal Pradesh. They concluded that the mafic magmatism is part of two distinct Paleoproterozoic mafic intrusive rocks occurring as small bodies of dikes, sills, and lenses.…”
mentioning
confidence: 99%